Tinjauan Literatur: Analisis Harga Pokok Produksi pada Penetapan Harga Jual Produk - Grace Stela Zane Simamora; Johs Charlos Hutabalian; Mawar Indah Juita Hutagalung; Khairani Alawiyah Matondang (Jurnal Ekonomi Manajemen dan Sekretari, 2024)
This study examines the significance of analyzing the Cost of Goods Sold (COGS) in determining product selling prices, particularly for Micro, Small, and Medium Enterprises (MSMEs). It evaluates the differences among full costing, variable costing, and traditional calculation methods in determining COGS and their respective impacts on selling prices. The objective is to offer recommendations to MSMEs for enhancing the accuracy of COGS calculations and improving competitiveness. The findings indicate that the full costing method yields more precise results and accounts for all production cost components, despite being more complex than other approaches. Consequently, training and simple technological solutions are essential to support MSMEs in adopting this method.